2008
DOI: 10.1111/j.1439-0531.2008.01230.x
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of In Vitro Culture Conditions on Embryo Development and Quality

Abstract: Despite major efforts directed at improving the yield of blastocysts from immature oocytes in vitro, the quality of such blastocysts continually lags behind that of blastocysts produced in vivo. These differences are manifested at the level of morphology, metabolism, gene expression and cryotolerance, and may have a knock-on effect further along the developmental axis. Evidence suggesting that in vitro culture conditions, while capable of producing blastocysts in relatively high numbers, are far from optimal w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
129
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(140 citation statements)
references
References 96 publications
(116 reference statements)
3
129
0
8
Order By: Relevance
“…This study showed that KLF4 localisation in both the in vitro and in vivo developed rabbit preimplantation embryos was diffused. As a transcription factor, KLF4 is expected to have a nuclear localisation as reported in the Macaque morulae and blastocysts [3]. The diffused localisation observed in the present study raises more questions related to delay in transport even though it possesses a nuclear localisation signal [55].…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…This study showed that KLF4 localisation in both the in vitro and in vivo developed rabbit preimplantation embryos was diffused. As a transcription factor, KLF4 is expected to have a nuclear localisation as reported in the Macaque morulae and blastocysts [3]. The diffused localisation observed in the present study raises more questions related to delay in transport even though it possesses a nuclear localisation signal [55].…”
Section: Discussionmentioning
confidence: 55%
“…Insight into these processes could serve to improve the efficiency of assisted reproduction technologies, development of transgenics, and to understand nuclear reprogramming. However, the embryos developed in vivo and in vitro show differences in their developmental potential [1][2][3] resulting from differences in gene expression patterns [4][5][6]. As the genes of mature spermatozoon and oocyte are silent, and remain inactive after fertilisation, maternal transcripts form a major source for mRNA during the initial stages of embryo development; until the zygotic Genome Activation (ZGA) occurs [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The resistance of the embryo to cryopreservation is one of the most useful parameters allowing an evaluation of the embryo quality [61]. A reliable embryo production system should be coupled with a cryopreservation protocol leading to improved survival rates after thawing/warming both in vitro and in vivo (i.e., pregnancies).…”
Section: Discussionmentioning
confidence: 99%
“…In the latter case, a small number of oocytes per female are usually recovered after OPU (approximately three to six oocytes recovered per nonstimulated cow and session; Rizos et al, 2005;Chaubal et al, 2006). IVEP efficiency has increased in recent years, although the quality of these embryos remains lower than in embryos produced in vivo (reviewed by Rizos et al, 2008). In particular, when embryos were cultured individually or in reduced groups, in addition to a lower efficiency of embryo production, the obtained embryos usually presented a lower number of cells per blastocyst (Paria and Dey, 1990;O'Doherty et al, 1997; Nagao et al, 2008: 5 v. 25 embryos).…”
Section: Introductionmentioning
confidence: 99%